ANALISIS KLASTERISASI NASABAH PENERIMA KREDIT MENGGUNAKAN METODE FUZZY C-MEANS - Shabir, Fadly (Yayasan Nusantara Hasana Berdikari, 2025)
This study conducted clustering of credit recipient customers using the Fuzzy C-Means (FCM) method. By using this clustering technique, customers can be grouped based on certain characteristics such as monthly income, credit history, business running time, and the amount of loan applied for. The results of the study indicate that the FCM method can provide more accurate customer segmentation in assessing credit risk and assisting banks in marketing strategies and risk mitigation. Thus, this study can be used as a reference in a data-based customer management system in the banking sector. The purpose of this study is to provide accurate segmentation of credit recipient customers. The use of FCM is expected to help reduce operational costs by directing resources to the right customers.